EXPERIMENTAL INVESTIGATION OF PROCESS PARAMETERS ON DIMENSIONAL ACCURACYIN MULTI-POINT FORMING PROCESS USING ANOVA ALGORITHM - Tahseen Fadhil Abbas, Karem MuhsonYounis & Khalida Kadhim Mansor (International Journal of Research Science and Management, 2019)
The multi-point forming (MPF) process is a modern pliable manufacturing technique utilized successfully in many industrial applications. In this work, the effect of many forming parameters was investigated which are blank holder, rubber cushion thickness and forming speed. Also, the influence of these parameters on the dimensional accuracy was studied, where the blank (sheet) material is brass with 0.71 mm thickness. This work concentrated on the development of predicted models to estimate the dimensional deviation using analysis of variance (ANOVA) to minimize the deviation of dimension in the multipoint forming process. Arithmetic minimum dimensional deviation was used as response parameter to assess the dimensional accuracy of multipoint formed parts. The data required was generated, compared and evaluated to the proposed models that obtained from the experiments.